Theoretical and experimental vibrational spectrum study of 4-hydroxybenzoic acid as monomer and dimer - Brandan, Silvia Antonia (2010)
Theoretical calculations on the molecular geometry and the vibrational spectrum of 4-hydroxybenzoic acid were carried out by the Density Functional Theory (DFT/B3LYP) method. In addition, IR and Raman spectra of the 4-hydroxybenzoic acid in solid phase were newly recorded using them in conjunction the experimental and theoretical data (including SQM calculations), a vibrational analysis of this molecular specie was accomplished and a reassignment of the normal modes corresponding to some spectral bands was proposed. The geometries of monomers and dimers in gas phase were optimized using the DFT B3LYP method with the 6-31G*, D95** and 6-311++G** basis sets. Also, both the vibrational spectra recorded and the results of the theoretical calculations show the presence of one stable conformer for the 4-hydroxybenzoic acid cyclic dimer. The B3LYP/6-31G* method was used to study the structure for cyclic dimer of 4-hydroxybenzoic acid and for a complete assignment our results were compared with results of the cyclic dimer of benzoic acid. A scaled quantum mechanical analysis was carried out to yield the best set of harmonic force constants. The formation of the hydrogen bond was investigated in terms of the charge density by the AIM program and by the NBO calculations.